1986
DOI: 10.4049/jimmunol.136.1.320
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the common acute lymphoblastic leukemia antigen (CALLA) on the surface of individual cells of human lymphoblastoid lines.

Abstract: Expression of the common acute lymphoblastic leukemia antigen (CALLA) on the surface of individual cells of the human lymphoblastoid lines CW678, Namalwa, and Nalm-6, and the distribution of the antigen epitopes within the cell populations have been determined quantitatively with the murine monoclonal anti-CALLA antibody J5. The distribution of CALLA epitopes in the cell populations was analyzed by indirect immunofluorescence measured by using flow cytometry. The average number of CALLA epitopes per cell were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The cell-surface glycoprotein CD10 is mainly expressed on lymphoid progenitors and terminal myeloid cells (neutrophils) in the hematologic system. [6][7][8] Previous studies have suggested that the function of CD10 in neutrophils may be related to various inflammatory responses. 28,29 However, in patients with NHL, whether the change in CD10 expression on the neutrophil surface could indicate a functional transformation, such as translation to G-MDSC-like morphological and functional characteristics, is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The cell-surface glycoprotein CD10 is mainly expressed on lymphoid progenitors and terminal myeloid cells (neutrophils) in the hematologic system. [6][7][8] Previous studies have suggested that the function of CD10 in neutrophils may be related to various inflammatory responses. 28,29 However, in patients with NHL, whether the change in CD10 expression on the neutrophil surface could indicate a functional transformation, such as translation to G-MDSC-like morphological and functional characteristics, is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…The cell‐surface glycoprotein CD10 is mainly expressed on lymphoid progenitors and terminal myeloid cells (neutrophils) in the hematologic system 6–8 . Previous studies have suggested that the function of CD10 in neutrophils may be related to various inflammatory responses 28,29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations